The acute effects of plyometric and sled towing stimuli with and without caffeine ingestion on vertical jump performance in professional soccer players - Guerra Jr, M. A.; Caldas, L. C.; De Souza, H. L.; Vitzel, K. F.; Cholewa, J. M.; Duncan, M. J.; Guimarães-Ferreira, L. (Journal of the International Society of Sports Nutrition, 2018)
Background: Post-activation potentiation (PAP) is the phenomenon by which muscular performance is enhanced in response to a conditioning stimulus. PAP has typically been evidenced via improved counter movement jump (CMJ) performance. This study examined the effects of PAP, with and without prior caffeine ingestion, on CMJ performance. Methods: Twelve male professional soccer players (23 ± 5 years) performed two trials of plyometric exercises and sled towing 60 min after placebo or caffeine ingestion (5 mg.kg- 1) in a randomized, counterbalanced and double-blinded design. CMJ performance was assessed at baseline and 1, 3 and 5 min after the conditioning stimulus (T1, T3 and T5, respectively). Results: Two way ANOVA main effects indicated a significant difference in jump height after the PAP protocol (F[3, 11] = 14.99, P < 0.001, partial 2 = 0.577). Analysis also indicated a significant difference in CMJ performance across conditions, with caffeine eliciting a greater response (F[1, 11] = 10.12, P = 0.009, partial 2 = 0.479). CMJ height was increased at T1, T3 and T5 in caffeine condition (5.07%, 5.75% and 5.40%, respectively; P < 0.01) compared to baseline. In the placebo condition, jump performance was increased at T3 (4.94%; P < 0.01) only. Jump height was higher in caffeine condition on T1, T3 and T5 (P < 0.05) but not on baseline (P > 0.05) compared to placebo. Conclusions: The results of this study suggest that acute plyometric and sled towing stimuli enhances jump performance and that this potentiation is augmented by caffeine ingestion in male soccer players.